Gadget Sebagai Pemasaran Digital Dan Branding Kelompok Tani Sumber Makmur Surabaya - afrizal andika; Akhyar Abdan Fillah; Ilham Prahardani; Bayu Dwi Hartomo; Muhammad Imam; Moch. Subechi Nurcahyo; Edelweis Putri Prima (Prapanca : Jurnal Abdimas, 2022)
Sumber Makmur Farmers Group located in Warugunung Flats Block Manyar B RT.4 / RW.3 Surabaya is a farmer group engaged in hydroponic-based horticultural crops, mostly dominated by housewives aged between 40-50 years. They use hydroponics as a side business to fulfill their needs. This Farmer Group still uses conventional marketing methods such as selling directly in the market or to certain agents, so that its marketing reach is relatively narrow and does not develop and is less ogled by the company. Based on the results of the survey, it was decided that group 11 would help Sumber Makmur Farmers Group to solve their capital problems with the right branding strategy to find potential investors.